2006
DOI: 10.1073/pnas.0608417103
|View full text |Cite
|
Sign up to set email alerts
|

The 10+4 microfibril structure of thin cartilage fibrils

Abstract: Determining the structure of cartilage collagen fibrils will provide insights into how mutations in collagen genes affect cartilage formation during skeletal morphogenesis and understanding the mechanism of fibril growth. The fibrils are indeterminate in size, heteropolymeric, and highly cross-linked, which make them refractory to analysis by conventional high-resolution structure determination techniques. Electron microscopy has been limited to making simple measurements of fibril diameter and immunolocalizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 28 publications
3
68
0
Order By: Relevance
“…To speculate, the α1(XI) collagen chain and in particular its N-propeptide domain may play a regulatory role in restricting the diameter of type II collagen fibrils assembled in developing cartilages. Exactly how the N-propeptide domain may affect fibril diameter is unclear, but recent structural analysis (Fallahi et al, 2005) and microfibril modeling predictions suggest that the N-propeptide globular domains are excluded from the microfibril interior, encircle the fibril and prevent further lateral aggregation of collagen molecules (Holmes and Kadler, 2006). The absence of α1(XI) chains from type V/XI hybrid molecules in cho/cho cartilage (Figure 2, tables 1, 2) may be responsible at least in part for an impaired regulation of type II collagen fibril diameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To speculate, the α1(XI) collagen chain and in particular its N-propeptide domain may play a regulatory role in restricting the diameter of type II collagen fibrils assembled in developing cartilages. Exactly how the N-propeptide domain may affect fibril diameter is unclear, but recent structural analysis (Fallahi et al, 2005) and microfibril modeling predictions suggest that the N-propeptide globular domains are excluded from the microfibril interior, encircle the fibril and prevent further lateral aggregation of collagen molecules (Holmes and Kadler, 2006). The absence of α1(XI) chains from type V/XI hybrid molecules in cho/cho cartilage (Figure 2, tables 1, 2) may be responsible at least in part for an impaired regulation of type II collagen fibril diameters.…”
Section: Discussionmentioning
confidence: 99%
“…Type XI collagen molecules are also cross-linked to type II collagen presumably as co-components of heterofibrils (Wu and Eyre, 1995). Since type XI collagen is proposed to be within the core of type II collagen fibrils (Mendler et al, 1989), it is becoming clear that type XI collagen may act as both the template for type II collagen fibrillogenensis and as a regulator of fibril diameter in cartilage (Blaschke et al, 2000;Holmes and Kadler, 2006;Wu and Eyre, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…According to these predictions, binding of A-domains as well as entire integrins could occur also to collagen fibrils. However, this notion is difficult to reconcile with the structural model of thin cartilage fibrils as proposed by Holmes and Kadler [46] in which, both, collagen II and XI molecules bearing potential integrin-binding sites are tightly packed into fibrils composed of 10 and 4 microfibrils located at the surface and the core of the fibrils, respectively. Thus, the accessibility of collagen molecules to integrins would be severely limited.…”
Section: Binding Of α1-or α2-integrin I-domains To Authentic Cartilagmentioning
confidence: 88%
“…Although no D-banding patterns were found along these fibrils, we suspect they are also type II collagen fibrils. Distinctively thin fibrils were noted before and it was suggested that thin fibrils may serve as a precursor for fibrilogenesis [13]. The sub-fibrillar structure of ~20 nm thin-fibrils was described by Holmes et al as a "10+4" arrangement of microfibrils, which contains a core of four microfibrils and a ring of ten surrounding microfibrils [13].…”
Section: Introductionmentioning
confidence: 99%
“…Distinctively thin fibrils were noted before and it was suggested that thin fibrils may serve as a precursor for fibrilogenesis [13]. The sub-fibrillar structure of ~20 nm thin-fibrils was described by Holmes et al as a "10+4" arrangement of microfibrils, which contains a core of four microfibrils and a ring of ten surrounding microfibrils [13]. These 4 nm thin microfibril are constructed by five tropocollagens in the equatorial plane [13,14].…”
Section: Introductionmentioning
confidence: 99%